Variation in the size of eggs and the numbers and distribution of testes in the tapeworm, Echinococcus granulosus: A. M. Al-Amery , S . S. Mhassen , A.H. Atia - Al-Amery, A. M. (The Iraqi Journal of Veterinary Medicine, 2009)
Morphological variation in helminthes parasites is a well- established phenomenon and may have manysources and important taxonomic implications. The morphological differences between the two isolates ofEchinococcus granulosus were the dimensions of worm total length , number of the developing segment ,testes distribution , details of the cirrus sac and position of genital pore .The results of present study indicatethat there is a form of the parasite is adapted to donkey and other in camel have some differences inmorphological also biological features not tackled in the present work .Genetic study is required for straindetection for clarification of the situation in a country .